The levels of Tafsīr ul-Qur’ān bi-l-Qur’ān (Interpretation of the Holy Qur’ān by the Qur’ān) in terms of authenticity and non-authenticity - Dr. Zobia Parveen (International Research Journal of Arabic and Islamic Studies, 2024)
The first source of the Tafsīr ul-Qur’ān bi-l-Qur’ān (interpretation of the Holy Qur’ān by the Qur’ān) is itself Qur’ān. Allah Almighty has clearly stated His commandments in various ways with repetitions at multiple places in the Holy Qur’ān. Allah Almighty sometimes mentions a matter briefly in one place in the Qur’ān and then explains it explicitly in another place. Therefore, when a commentator interpreting it, he should, first of all, explain the Qur’ān with the Qur’ān itself. So gather all the repeated verses related to a particular topic and compare these verses with one another so that what is briefly mentioned in one place can understand with the help of what is described in detail, and the ambiguous can be clarified by the explicit. The Tafsīr ul-Qur’ān bi-l-Qur’ān is esteemed by scholars as the highest form of exegesis. But scholars are differ on its absolute acceptance. Some fully endorse it, while others question its complete authenticity due to misuse by misguided sects. Consequently, its authenticity and acceptability cannot be unconditionally accepted or rejected. So, all exegesis of the Qur’ān by the Qur’ān is not equally credible and there are various levels and categories of the Tafsīr ul-Qur’ān bi-l-Qur’ān and they are vary in strength and rank. The primary reason for the differing opinions on interpretation of the Qur’ān by the Qur’ān is whether it falls under Tafsīr bil-Mathu̅r (exegesis based on transmitted reports) or Tafsīr bir-rāʼe (exegesis based on opinion). Determining its category depends on the commentator and the sources that are used to get it. Scholars who view it as Tafsīr bil-Mathu̅r see it as absolutely acceptable, while those who consider it Tafsīr bir-rāʼe do not fully endorse its authenticity. If the Tafsīr ul-Qur’ān bi-l-Qur’ān is explicitly from Allah or issued from the Holy Prophet PBUH or there is consensus on it, then its authenticity. When a Sahabī (companion) or Tabi’i (Successor) interprets the Qur’ān by the Qur’ān, it holds the same status as the tafsīr of the Sahabī and Tabi’i. However, if it involves disapproved interpretative opinions driven by personal desires or false beliefs, it is rejected. Acceptable interpretations are those that are free from personal biasedness and supported by valid evidence.